2016
DOI: 10.1213/ane.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity and Specificity of Pulmonary Carbon Dioxide Elimination for Noninvasive Assessment of Fluid Responsiveness

Abstract: PEEP-induced changes in VCO2 predicted fluid responsiveness with accuracy in patients undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…Patients with multiple sources of pulmonary blood flow, including patients with significant collateral blood flow, were excluded due to potential inaccuracy in the assessment of Q P . Patients with passive pulmonary blood flow (bidirectional Glenn or Fontan physiology) were also excluded due to potential inaccuracies in the assessment pulmonary blood flow resulting from variable contributions from systemic to pulmonary collateral flow . Finally, patients on extracorporeal membrane oxygenation (ECMO) at the time of cardiac catheterization, and patients with non‐English‐speaking parent/guardian were also excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with multiple sources of pulmonary blood flow, including patients with significant collateral blood flow, were excluded due to potential inaccuracy in the assessment of Q P . Patients with passive pulmonary blood flow (bidirectional Glenn or Fontan physiology) were also excluded due to potential inaccuracies in the assessment pulmonary blood flow resulting from variable contributions from systemic to pulmonary collateral flow . Finally, patients on extracorporeal membrane oxygenation (ECMO) at the time of cardiac catheterization, and patients with non‐English‐speaking parent/guardian were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Fontan physiology) were also excluded due to potential inaccuracies in the assessment pulmonary blood flow resulting from variable contributions from systemic to pulmonary collateral flow. 20 Finally, patients on extracorporeal membrane oxygenation (ECMO) at the time of cardiac catheterization, and patients with non-English-speaking parent/guardian were also excluded. metric capnography by the respiratory rate.…”
Section: Patients With Passive Pulmonary Blood Flow (Bidirectional Glmentioning
confidence: 99%
“…In a recent study in patients undergoing cardiac surgery, fluid responsiveness was predicted by the haemodynamic effects of a sudden increase in positive end-expiratory pressure from 5 to 10 cmH 2 O. The effects were measured through CO 2 elimination, which was used as a surrogate of cardiac output in these patients who were well sedated [78]. The respiratory systolic variation test (RSVT) quantifies the decrease in systolic pressure in response to a standardised manoeuvre consisting of three consecutive mechanical breaths with increasing airway pressure.…”
Section: … and Other Tests Using Heart–lung Interactionsmentioning
confidence: 99%
“…It has been shown that P ET CO 2 directly correlates to CO and can sufficiently predict fluid responsiveness when combined with PLR testing [70,71]. Tusman et al [72] introduced a further method based on volumetric CO 2 measurements by quantifying the amount of exhaled CO 2 instead of the concentration. To detect a lack of intravascular fluids, the pa-tient´s fluid responsiveness was provoked with an elevation of PEEP from 5 to 10 cmH 2 O for one minute.…”
Section: Novel Physiological Tests For Predicting Fluid Responsivenessmentioning
confidence: 99%
“…Furthermore, a ROC-analysis revealed a high predictive performance that was superior to the change of end-tidal CO 2 concentration and PPV. Even though this method is only available in ventilated patients, it offers a non-invasive and accurate approach for predicting fluid responsiveness that is worthy of further validation [72,73].…”
Section: Novel Physiological Tests For Predicting Fluid Responsivenessmentioning
confidence: 99%